Fractal-Based Image Encoding and Compression Techniques - Drakopoulos, Vasileios (Communications - Scientific Letters of the University of Zilina, 2013)
In computer science and information theory, data compression, source coding, or bit-rate reduction is the process of encoding digital information using fewer bits than the original representation. Specifically, digital-image compression is important due to the high storage and transmission requirements. Various compression methods have been proposed using different techniques to achieve high compression ratios. Fractal image encoding is a technique based on the representation of an image by contractive transformations. Fractal-based image compression methods belong to different categories according to the different theories they are based on. In this article, first we try to clarify the terminology used and then to comprehensively unveil the mathematical principle behind fractal image compression as well as to briefly overview a variety of schemes that have been investigated.
Keywords: approximation; coding; dimension; fractal; image compression; image encoding; interpolation; iterated function system; local; partitioned; recurrent; transformation